Identification of Key Genes Related to Postnatal Testicular Development Based on Transcriptomic Data of Testis in Hu Sheep - Xu, Haiyue; Sun, Wu; Pei, Shengwei; Li, Wanhong; Li, Fadi; Yue, Xiangpeng (Frontiers in Genetics, 2022)
Selection of testis size can improve the reproductive capacity of livestock used for artificial insemination and has been considered as an important strategy for accelerating breeding process. Although much work has been done to investigate the mechanisms of testis development in various species, there is a little information available in regard to the differences in transcriptomic profiling of sheep testes at different developmental stages. In this work, we aimed to identify differentially expressed genes (DEGs) by RNA-Seq in sheep during different growth stages, including 0 mouth old (infant, M0), three months old (puberty, M3), six months old (sexual maturity, M6) and twelve months old (body maturity, M12). A total of 4606 (2381 up and 2225 down), 7500 (4368 up and 3132 down), 15 (8 up and 7 down) DEGs were identified in M3_vs_M0, M6_vs_M3 and M12_vs_M6 comparsion, respectively. Of which, a number of genes were continuous up-regulated and down-regulated with testicular development, including ODF3, ZPBP1, PKDREJ, MYBL1, PDGFA, IGF1, LH, INSL3, VIM, AMH, INHBA, COL1A1, COL1A2, and INHA. GO analysis illustrated that DEGs were mainly involved in testis development and spermatogenesis. KEGG analysis identified several important pathways and verified several reproduction-associated DEGs such as COL1A1, COL1A2, PDGFA, and IGF1. In addition, two gene modules highly associated with testis development and core genes with testis size were identified using weighted gene co-expression network analysis (WGCNA), including hub genes positively associated testis size such as RANBP9, DNAH17, SPATA4, CIB4 and SPEM1, and those negatively associated with testis size such as CD81, CSK, PDGFA, VIM and INHBA. This study comprehensively identified key genes related to sheep testicular development, which may provide potential insights for understanding male fertility and better guide in animal breeding.